Pemanfaatan Aplikasi Photomath Sebagai Media Belajar Matematika pada Materi Matriks: Systematic Literature Review - Fadillah, Dhea Tri; Yahfizam, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research seeks to define the goals of incorporating the Photomath application into mathematics education, particularly concerning matrix-related subjects, utilizing the Systematic Literature Review (SLR) methodology. This study contributes to the existing knowledge base, serving as a valuable reference for subsequent research endeavors. The anticipated outcomes of this research aim to provide profound insights and essential guidance for the development of innovative approaches to teaching mathematics, leveraging the Photomath application to enhance student understanding of matrix-related concepts.